Rhodococcus sp. YHY01 a microbial cell factory for the valorization of waste cooking oil into lipids a feedstock for biodiesel production - Bhatia, Shashi Kant; Gurav, Ranjit; Choi, Yong Keun; Lee, Hong Ju; Kim, Sang Hyun; Suh, Min Ju; Cho, Jang Yeon; Ham, Sion; Lee, Sang Ho; Choi, Kwon Young; Yang, Yung Hun (Fuel, 2021)
Biodiesel is an environmentally friendly, biodegradable, and renewable source of energy. It can be used as an alternate source of energy to reduce overburden on fossil-based fuels. The use of waste cooking oil (WCO) for biodiesel production may solve its management problem and provide additional revenue. Rhodococcus is an oleaginous microbe that can utilize various feedstock as a carbon source for growth and lipid production. In this study, WCO was used as a carbon source and the effect of various surfactants on growth and lipids accumulation was studied. Production media components optimized using response surface design and cultivation in optimized media i.e., WCO (1.15%): NH4Cl (0.09%): NaCl (0.97%): PEG (0.05%) resulted in 3.42 ± 0.06 g CDW/L biomass production, 2.39 ± 0.04 g/L lipid production with 70 ± 4.0% w/w lipid accumulation. Produced lipids were analyzed for fatty acid methyl esters (FAMEs) composition and composed of palmitoleic acid (16:1, 61.68%) > palmitic acid (C16:0, 21.48%) > myristic acid (C14:0, 12.95%) > stearic acid (C18:0, 2.35%) > pentadecanoic acid (C15:0, 0.74%) > heptadecanoic acid (C17:0, 0.72%) > oleic acid (C18:1, 0.05%). Properties of biodiesel depend on FAMEs composition and analyzed as cetane number (CN, 56.5), iodine value (IV, 63.7), cold filter plugging point (CFPP, −9.6), cloud point (CP, 6.3 °C), pour point (PP, 0.028 °C), oxidation stability (OS, infinity), high heating value (HHV, 38.9), kinematic viscosity (υ, 3.2 mm2/s), and density (ρ, 0.87 g/cm3). The properties of produced biodiesel satisfy the international standards EN14214 and IS15607 and suggest that biodiesel produced from WCO oil can be used as an energy source.
Keywords: A-carbon; Biodiesel production; Carbon source; Energy; Lipid productions; Renewable; Rhodococcus; Sources of energy; Valorisation; Waste cooking oil; Biodiesel; Energy; Renewable; Rhodococcus; Valorization; Waste cooking oil